ROLE OF JIPMER AND RAJIV GANDHI HOSPITAL FOR WOMEN AND CHILDREN TOWARD PROTECTING PEOPLE’S HEALTH IN PUDUCHERRY: AN EMPIRICAL STUDY - Dr.R.Saravanan, A.Thileeban (International Journal of Modern Agriculture, 2021)
Issues and problems of people in overall Indian territory is known as a primary and prime concern of the central government, state government and union territory, because people health was understood by all the people and administration as a core base of all types development and progress ,without which no nation, country ,state and family could be developed and progressed .All these elements are developing and progressing its administrative entity and governance efficiency along with the help and support of people’s good health and energy .From family to nation people’s healthy health is contributing huge and vastly in its development ,success and ameliorations ,good health status of people of a country is reflecting in its political development, agricultural progress, industry development, efficient administration and education advancement ,its people good health status determines about success and victory of all its international cooperation and policy making because human power or capital is most needful power and essential elements in a countries’ international and domestic achievements and success ,from these patterns every state government is making different and unique health related polices and laws with an interest to augment and amplify its political, economic ,agricultural ,educational ,administrative, corporate and industry developments .Good health is being as a epicentre of both human being life as well as in government developments thereby family to country getting so many success and attaining all types of needful progress in its political and administrative developments. Giving an importance to people health preservation and protection has been paid colossal and close attention by all state and central government from post Independence onwards with an interest to fortify and strengthen India’s human resource, economic developments and promote India’s international cooperation by showing its mammoth human resources power and energy. A nation or family could be identified by its people’s good health status thereby it will get supports, famous, recognition and praise from the neighbourhood and international people. Unless nation or a family have above quoted good health system it will be understood and estimated as a poor nation and family which will get much stuff to lift its national economy as equal to international economy as a family is suffering to promote its income status due to having meagre health status .As to strengthen family income ,revenue and protect old aged people’s health and facilities it must have healthy successor and descendant, without having such healthy members or person in a family it will suffer just like boneless item, in this regard a nation also will suffer lot and immensely in terms of increasing and developing its economic ,military and agricultural developments because for develop both family and nation they must have strong and steady health status ,for which government have to pay prime and first hand attention on strengthening health status of the citizens .Strong and steady health status are not only being applied by family and nation on generating income and developing economic status of a country but it also used and applied toward protecting of nation sovereignty and territory from the attacks and usurpation of the host country’s military forces.